Precision Nutrition and Metabolic Syndrome Management - Alfredo J. Martínez (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Precision nutrition is an emerging concept encompassing an integrated action considering not only the genetic/epigenetic makeup and ethnic aspects of individuals, but other personalized phenotypical features, such as family and individual clinical issues, previous diseases and therapeutic treatments, perinatal nutrition, food likes/dislikes, allergies/intolerances, lifestyle attitudes and patterns, social and cultural circumstances or religious beliefs, etc. In this context, chronic disease prevalence is a global public health problem itself, which is also accompanied by a number of complications, including insulin resistance, hypertension, hypercholesterolemia, fatty liver, inflammation, oxidative status and immunocompetence disturbances, and other adverse manifestations related to metabolic syndrome, which may need individualized nutritional approaches. Therefore, the current Special Issue attempts to provide specific nutritional strategies to prevent or treat the complications associated with metabolic syndrome features concerning diabetes, vascular events, liver diseases, dyslipemia, and cancer with a precision nutrition scope.